Strategic Management of Islamic Educational Institutions to Improving Education Quality - Sihotang, Ijah Mulyani; Syamsuyurnita, Syamsuyurnita; Fatmawarni, Fatmawarni (IJOSMAS, 2022)
This study focuses on how Islamic education management is implemented, particularly at Muhammadiyah Medan Islamic Elementary School.The researcher used a case study research design and a qualitative research method in this study.Interviews, observations, and written records were used to gather information.Following data presentation and drawing conclusions, techniques for data reduction were used to analyze the data.The study's findings are as follows:1) At Muhammadiyah Medan Islamic Elementary School, strategy is created by first creating a vision and mission that take into account both the internal and external environment. Next, goals and targets are set, and strategy is set.2) At Muhammadiyah Medan Islamic Elementary School, activities outline the strategies that have been developed in order to implement them.The activity coordinator, who works with the school principal to coordinate, is in charge of the technical implementation.In order to implement the monitoring system, extensive communication and routine control with the activity coordinator are implemented.3) Both formal and informal meetings are used to implement the Muhammadiyah Medan Islamic Elementary School's evaluation strategy.Both the internal level and the field as a whole hold formal meetings on a regular basis.based on the findings of this study, better management can be implemented in the future to improve Islamic educational institutions